THE PROBLEM OF METHODOLOGY FOR HISTORICAL- PSYCHOLOGICAL RESEARCH - Maslyuk, Andrii (PSYCHOLOGICAL JOURNAL, 2019)
The problem of the methodology for historical-psychological research is examined through the prism of the national philosophical and psychological science. The starting point of the methodology is the works of V. Romenets, Yu. Rozhdestvensky, V. Gorsky and others. Original texts contain a significant informational layer that must be skillfully highlighted and interpreted, taking into account their authors’ life and professional paths, the dynamics of the authors’ experience throughout life and the influence of the culturally-historical era on their psychological achievements. The methods for historical and psychological research analysis are clarified: comparative-descriptive; historical and documentary; ontologically oriented ones and the peculiarities of their applications are disclosed. V. Gorsky investigates the features of historical-philosophical (psychological) analysis of an author’s text through the prism of contextual, outside of contextual and situational analyses. The context can remove multiple meaning of a word, indicating its specific meaning, built-in by the text author. At the same time, a researcher, by examining a text, must bear in mind changes appeared in time concerning the meanings of used terms and not transfer the modern understanding of used concepts at analyses of texts belonging to the past centuries. It is still necessary to find out subtexts, remained unrevealed due to certain reasons. A researcher should understand a studied scientist’s style, which identifies the scientist and, at the same time, manifests specific historical conditions and shows the scientist’s way of mastering the culture; and these efforts contribute to adequate knowledge of the examined text, penetration into its spiritual core. The article notes that the situational analysis has its own characteristics, which consist in a historian’s understanding of psychology of all circumstances that shaped an examined scientist’s worldview and the peculiarities of the audience to which the scientist addresses his/her texts. When carrying out a situational analysis, a historian-psychologist must take into account the social-economic, political conditions influencing formation of an author’s opinion expressed in the examined text and be aware of the relation of this opinion with the contests between psychological ideological directions. The attention is focused on the mistakes that researchers can make by analyzing the text.